ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA BAYI DI PUSKESMAS REWARANGGA - YUSTINA PACIFICA MARIA PASCHALIA (Poltekkes Kemenkes Kupang, 2017)
Introduction: Breastfeeding has an important role to support the growth, health and survival of infants because breast milk is rich in nutrients and antibodies. The Government of Indonesia through the Ministry of Health also recommends mothers to breastfeed exclusively for six months to baby (Riskesda, 2013). Method: The purpose of this study to determine the factors that influence exclusive breastfeeding in infants. This research includes quantitative analytical research with cross sectional design. The population is all the mothers in Puskesmas Rewarangga that at the time of the study had infants aged 6-12 months. Samples were selected purposively with a sample size of 68 people test analysis using the chi square statistic. To obtain a significant risk factor in the confidence level of 0.05 and 95% confidence interval (α = 0.05) using the Odds Ratio.Result: The results showed that there was no correlation between maternal age with exclusive breastfeeding (p = 1.000), there is a relationship between maternal education with exclusive breastfeeding (p = 0.013), there is no relationship between the mother's occupation with exclusive breastfeeding (p = 0.769) , there is a relationship between family income with exclusive breastfeeding (p = 0.013), there was no correlation between the number of family members with exclusive breastfeeding (p = 0.457), there was no correlation between habitual ANC with exclusive breastfeeding (p = 0.225), no there is a relationship between birth attendant last with exclusive breastfeeding (p = 0.779).Conclusion: In general it can be concluded that the factors influencing the exclusive breastfeeding in infants in Puskesmas Rewarangga is maternal education and family income.